2022
DOI: 10.1177/20451253221122526
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-acting injectable antipsychotics on hospitalizations and global functioning in schizophrenia: a naturalistic mirror-image study

Abstract: Background: Partial adherence to antipsychotics is the most common cause of relapses and rehospitalization in patients with schizophrenia (SZ), leading to higher health care costs and psychosocial disability. The use of long-acting injectable (LAI) antipsychotics may improve therapeutic continuity and adherence to treatment. Objective: To assess the effectiveness of switching from oral antipsychotics (OAs) to long-acting antipsychotics. Methods: This 1-year mirror-image study evaluated the effect of switching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…This may result from bias in the recruitment of RCT participants that produces a population more likely to be adherent to treatment (i.e., selecting for participants with less severe disease, fewer comorbidities, superior cognition, and greater motivation) and excludes those more likely to be prescribed LAIs in actual practice (Haddad et al, 2009). Furthermore, RCTs often provide comprehensive follow up that can improve outcomes regardless of pharmacological intervention (Montemagni et al, 2022), which may have contributed to a lack of benefit reported with LAIs in some studies (Kishimoto et al, 2014). Ultimately, the significance of these methodological differences remains unclear as a recent meta-analysis of RCTs and cohort studies demonstrated efficacy of LAIs in reducing risk of hospitalization or relapse compared to oral antipsychotics regardless of study type (Kishimoto et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This may result from bias in the recruitment of RCT participants that produces a population more likely to be adherent to treatment (i.e., selecting for participants with less severe disease, fewer comorbidities, superior cognition, and greater motivation) and excludes those more likely to be prescribed LAIs in actual practice (Haddad et al, 2009). Furthermore, RCTs often provide comprehensive follow up that can improve outcomes regardless of pharmacological intervention (Montemagni et al, 2022), which may have contributed to a lack of benefit reported with LAIs in some studies (Kishimoto et al, 2014). Ultimately, the significance of these methodological differences remains unclear as a recent meta-analysis of RCTs and cohort studies demonstrated efficacy of LAIs in reducing risk of hospitalization or relapse compared to oral antipsychotics regardless of study type (Kishimoto et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This study investigated the neuroprotective property of the BCG vaccine against haloperidol-induced TD-like orofacial dyskinesia and motor abnormalities. Haloperidol is a first-generation typical antipsychotic agent used to manage schizophrenia [33]. However, its long-term use is reported to cause hyperkinetic orofacial dyskinesia, also known as TD [34].…”
Section: Discussionmentioning
confidence: 99%